2011
DOI: 10.1007/s12686-011-9432-5
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of polymorphic microsatellite loci in the migratory freshwater fish Prochilodus lineatus (Characiformes: Prochilodontidae)

Abstract: Thirteen new polymorphic microsatellite loci were developed and tested in 57 individuals from three locations along the Paraná River. All loci were polymorphic, with 2-22 alleles per locus. Cross-species amplifications were successful for all loci in four other Prochilodus species, suggesting that these microsatellites will be useful for investigation of genetic variation and structure in Prochilodus populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
1
9

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 10 publications
2
7
1
9
Order By: Relevance
“…Seven microsatellite loci were selected from two sets previously described for P. lineatus; PL 34, PL139, PL 119 (Rueda et al 2011) andPli 30, Pli 34, Pli 43, Pli 60 (Yazbeck andKalapothakis 2007). For genotyping on an automated sequencer, the forward primer of each locus was labeled with an additional M13 sequence (5 0 -TGTAAAACGACGGCCAGT-3 0 ) at the 5 0 end, allowing fluorescent labeling of the PCR products using M13 fluorescent labeled primers (Schuelke 2000).…”
Section: Microsatellite Markersmentioning
confidence: 99%
“…Seven microsatellite loci were selected from two sets previously described for P. lineatus; PL 34, PL139, PL 119 (Rueda et al 2011) andPli 30, Pli 34, Pli 43, Pli 60 (Yazbeck andKalapothakis 2007). For genotyping on an automated sequencer, the forward primer of each locus was labeled with an additional M13 sequence (5 0 -TGTAAAACGACGGCCAGT-3 0 ) at the 5 0 end, allowing fluorescent labeling of the PCR products using M13 fluorescent labeled primers (Schuelke 2000).…”
Section: Microsatellite Markersmentioning
confidence: 99%
“…In previous studies, microsatellites loci in closely related species have been identified. These include species belonging to the Anostomidae [163], Characidae [164,165], Cichlidae [166], Pimelodidae [167], Prochilodontidae [168][169][170] and Serrasalmidae [171] families.…”
Section: Next Generation Sequencing (Ngs) In Molecular Marker Discoverymentioning
confidence: 99%
“…La diversidad genética fue analizada usando 6 loci microsatélites previamente aislados y caracterizados para Prochilodus lineatus por Rueda et al, (2011), Prochilodus costatus por Carvalho-Costa et al, (2006) y Pseudoplatystoma corruscans por Revaldaves et al, (2005) (tabla 1).…”
Section: Amplificación De Los Microsatélitesunclassified
“…Sitios de muestreo: (a) río La Miel en el departamento de Caldas, (b) río Ranchería en el departamento de la Guajira. (Rueda et al, 2011), Prochilodus costatus (Carvalho-Costa et al, 2006) y Pseudoplatystoma corruscans (Revaldaves et al, 2005) …”
Section: Amplificación De Los Microsatélitesunclassified
See 1 more Smart Citation